2020
DOI: 10.3390/fluids5040178
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Different Unsteady Incident Flow Environments on Drag Measurements in an Open Jet Wind Tunnel

Abstract: Aerodynamic development for road vehicles is usually carried out in a uniform steady-state flow environment, either in the wind tunnel or in Computational Fluid Dynamics (CFD) simulations. However, out on the road, the vehicle experiences unsteady flow with fluctuating angles of incidence β, caused by natural wind, roadside obstacles, or traffic. In order to simulate such flow fields, the Forschungsinstitut für Kraftfahrwesen und Fahrzeugmotoren Stuttgart (FKFS) swing® system installed in the quarter scale mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This approach was pioneered by Cogotti, [16], with the Turbulence Generating System, (TGS), in the Pininfarina full-scale wind tunnel, while similar model scale facilities have been built at FKFS, [17], and Durham University, [18]. A recent investigation by Fei et al, [19] using the model wind generator (SWING) system at FKFS with two DrivAer and two SAE model configurations found that for three configurations the unsteady drag coefficient variation with turbulence intensity was predicted using a quasi-steady approach based on the yaw angle distribution. For the other configuration the drag rise with turbulence was correctly predicted but was higher than the experimental results by approximately ΔCD = 0.004.…”
Section: Wind Tunnel Simulation Represents a Uniform Steady Crosswindmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach was pioneered by Cogotti, [16], with the Turbulence Generating System, (TGS), in the Pininfarina full-scale wind tunnel, while similar model scale facilities have been built at FKFS, [17], and Durham University, [18]. A recent investigation by Fei et al, [19] using the model wind generator (SWING) system at FKFS with two DrivAer and two SAE model configurations found that for three configurations the unsteady drag coefficient variation with turbulence intensity was predicted using a quasi-steady approach based on the yaw angle distribution. For the other configuration the drag rise with turbulence was correctly predicted but was higher than the experimental results by approximately ΔCD = 0.004.…”
Section: Wind Tunnel Simulation Represents a Uniform Steady Crosswindmentioning
confidence: 99%
“…This paper is based completely on the assumption that the effect of turbulence in the atmosphere can be predicted using a quasi-steady approach as suggested from the study by Fei et al, [19]. The authors of that paper make the comment that the turbulence generated by the moving vanes in their wind tunnel may lack some high frequency Cooper and Campbell, [21], found that their quasi-steady theory, when compared with drag data for model scale trucks in grid generated turbulence in the wind tunnel, gave qualitatively correct results but underestimated the magnitude of the changes due to turbulence.…”
Section: Quasi-steady Theorymentioning
confidence: 99%